2019
DOI: 10.1038/s41598-018-37487-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lure Combination on Fruit Fly Surveillance Sensitivity

Abstract: Surveillance for invading insect pests is costly and the trapper usually finds the traps empty of the target pest. Since the successful establishment of new pests is an uncommon event, multiple lures placed into one trap might increase the efficiency of the surveillance system. We investigated the effect of the combination of the Tephritidae male lures – trimedlure, cuelure, raspberry ketone and methyl eugenol – on catch of Ceratitis capitata , Zeugodacus cucurbitae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…In addition, earlier work typically used trap/lure dispenser/ toxicant combinations that differed greatly from the specific combination being appraised as the program-wide replacement for liquid methyl eugenol. Briefly, previous research often used wafers and not plugs (e.g., Vargas et al 2009;Shelly 2010;Leblanc et al 2011;Wee & Shelly 2013;Stringer et al 2019). As noted above, however, wafers are impractical for large-scale trapping programs, because placing them in Jackson traps is a cumbersome and time-consuming process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, earlier work typically used trap/lure dispenser/ toxicant combinations that differed greatly from the specific combination being appraised as the program-wide replacement for liquid methyl eugenol. Briefly, previous research often used wafers and not plugs (e.g., Vargas et al 2009;Shelly 2010;Leblanc et al 2011;Wee & Shelly 2013;Stringer et al 2019). As noted above, however, wafers are impractical for large-scale trapping programs, because placing them in Jackson traps is a cumbersome and time-consuming process.…”
Section: Discussionmentioning
confidence: 99%
“…These attractants are Methyl isoeugenol also used in the surveillance system targeting more than one species at a time and are a powerful monitoring tool for the early detection of a species and population monitoring. Stringer et al (2019) reported that in fruit fly management using various lure combinations reduces the cost of operation. Recently in Oceania and Asia, more attractive male lures (isoeugenol, methylisoeugenol, dihydroeugenol, and zingerone) were identified for several weakly CL-and methyl eugenol (ME) responsive species (Royer et al, 2019).…”
Section: Male Luresmentioning
confidence: 99%
“…Monitoring systems are suggested for the control, eradication, and suppression of fruit flies by trapping systems (Manrakhan et al 2017). Fruit fly trapping systems often use odors such as pheromones, host plant volatiles, and chemical compounds to attract the insects to a trap (Stringer et al 2019). The use of chemical compounds is one way to monitor and manage fruit flies.…”
Section: Introductionmentioning
confidence: 99%